Effect of Professional Ethics, Audit Quality, and Workload on Materiality Levels Consideration - Ni Wayan Rustiarini; I Kadek Listawan; Ni Putu Shinta Dewi (Management and Sustainable Development Journal, 2021)
The level of materiality is a professional judgment that affects the auditor's perception of the needs of those who have sufficient knowledge and who place confidence in the financial statements. Materiality relates to decision making that will give rise to confidence in users of financial statements that the financial statements are free from material misstatement and are by accounting principles. This study aims to examine and obtain evidence of the influence of professional ethics, audit quality, and workload on the consideration of Bali public accounting firms' materiality levels. The study population was auditors at Bali's public accounting firm, registered in the Ikatan Akuntan Public Indonesia Directory, which was still active until 2020. The sample in this study was 80 respondents who were determined based on the purposive sampling method. The analytical tool used to test the hypothesis is multiple linear regression. The results showed that professional ethics and audit quality had a positive effect on the materiality level. Meanwhile, the workload does not affect the materiality level consideration.